Efficacy and safety of limb position on blood loss and range of motion after total knee arthroplasty without tourniquet: A randomized clinical trial. (December 2018) - Wu, Yuangang; Lu, Xiaoxi; Ma, Yimei; Zeng, Yi; Xiong, Huazhang; Bao, Xianchao; Shen, Bin
Abstract: Background: The purpose of this study was to investigate the effect of postoperative limb position on blood loss and knee function after primary total knee arthroplasty without tourniquet. Material and methods: One hundred patients were randomly assigned into 2 groups: Group A was given a knee flexion position at 60° for 24 h after surgery but without the tourniquet use. Patients in group B was received the tourniquet use the same flexion position as the Group A. All patients received intravenous (IV) tranexamic acid (TXA) 15 mg/kg before skin incision and another 1 g of IV-TXA after 3 h. Results: The total blood loss was similar in the 2 groups. Group A had significantly less hidden blood loss and drainage volume (P = 0.023, P < 0.001), and higher intraoperative blood loss than the Group B (P < 0.001). The visual analog scale and knee circumference in Group A were lower than the Group B on postoperative days 1, 3 and 5. The range of motion was also lowering in Group A than the Group B on postoperative days 1, 3, 5 and at the 1 month. No significant differences (P > 0.05) were observed between the 2 groups regarding maximum hemoglobin drop, transfusion rate, postoperative hospital stay, DVT and/or PE, and wound-related complications. Conclusion: Based on the current evidence, patients treated with postoperative limb positions without a tourniquet can effectively reduce hidden blood loss and drainage volume, as well as better early clinical benefits than those treated with a tourniquet. Level of evidence: Therapeutic Level I. Highlights: We compared the effect of the limb positions in TKA without tourniquet. Patients with no tourniquet therapy have a better early clinical benefit. No postoperative complications were found in the two groups.